1973
DOI: 10.1029/ja078i013p02001
|View full text |Cite
|
Sign up to set email alerts
|

Anomalously low proton temperatures in the solar wind following interplanetary shock waves-evidence for magnetic bottles?

Abstract: Occasionally, anomalously low values of the solar wind proton temperature Tp are observed when the solar wind velocity v is high. A large fraction of such measurements by the Vela 3 satellites follow the passage of interplanetary shocks by some 20-60 hours. Of 24 postshock events in which v exceeded 400 km sec -x and for which Vela 3 measurements are available, 12 exhibited plasma states of anomalously low Tp, high v. The proton density at the time of these observations typically was depressed below normal, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
140
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(150 citation statements)
references
References 24 publications
7
140
0
3
Order By: Relevance
“…However, temperature depressions are considered one of the best indicators of the CME related material in the solar wind (e.g. Gosling, Pizzo, and Bame, 1973;Richardson and Cane, 1995). An example of a temperature depression event observed by Wind is given in Figure 6 (Event E11).…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, temperature depressions are considered one of the best indicators of the CME related material in the solar wind (e.g. Gosling, Pizzo, and Bame, 1973;Richardson and Cane, 1995). An example of a temperature depression event observed by Wind is given in Figure 6 (Event E11).…”
Section: Observationsmentioning
confidence: 99%
“…We searched for the intervals with decreased magnetic field variability, smooth rotation of the magnetic field and clear decreases in the proton temperature (T p ) and proton beta. Solar wind temperature depressions are considered as one of the most reliably ICME identifiers (Gosling, Pizzo, and Bame, 1973;Richardson and Cane, 1995). Using the empirical correlation between solar wind speed and proton temperature (Lopez, 1987) to calculate the "expected proton temperature" (T ex ) Richardson and Cane (1995) found that ICMEs typically have T p /T ex < 0.5.…”
Section: Introductionmentioning
confidence: 99%
“…These speculations stemmed from the attempts to explain geomagnetic disturbances (e.g., Lindeman 1911;Chapman and Ferraro 1929;Bartels 1932) and so-called Forbush decreases in cosmic ray intensities (Forbush 1937;Morrison 1956;Cocconi et al 1958;Piddington 1958). The first ICME observations emerged in the 1970s suggesting loop-or bubble-like structures behind interplanetary shocks (e.g., Hirshberg et al 1970;Gosling et al 1973;Palmer et al 1978). For a more detailed historical review on ICMEs, and their role in understanding solar-terrestrial relationships, we guide the reader to Gopalswamy (2016).…”
Section: Introductionmentioning
confidence: 99%
“…ICMEs are identified by several characteristic features in the interplanetary medium, as reviewed by Gosling (1990) and Neugebauer and Goldstein (1997). Solar wind signatures of ICMEs include the increase of He ++ (Hirshberg et al, 1972;Borrini et al, 1982), the abnormally low proton temperature (Gosling et al, 1973;Richardson and Cane, 1995), the bidirectional electron heat flow (Gosling et al, 1987), and the magnetic cloud (Burlaga et al, 1981;Marubashi, 2000;Lepping et al, 2006), though the regions of these ICME signatures do not necessarily coincide with each other.…”
Section: Introductionmentioning
confidence: 99%